Predicting Pro-Environmental Behavior for Managing Farmer-Wildlife Conflicts in Northern Iran - Mojgan Asadollahi; Faraham Ahamadzadeh; Hossein Mahmoudi (Sustainable Earth Trends, 2023)
Effectively managing and mitigating “human-wildlife conflict” (HWC) by adjusting the use of cultivated land to realize the coexistence of humans and wildlife plays an important role in protecting biodiversity, ensuring food security, improving cultivated land use efficiency, and improving the livelihoods of community residents in nature reserves. Moreover, conservation biologists are paying growing attention to HWC, which is a significant global environmental problem. To achieve a sustainable solution and mitigate such conflict, it is necessary to focus on the conflict’s human dimensions and direct and indirect economic and social effects. Human behaviors are affected by values, attitudes, norms, and economic factors. Thus, identifying those factors might be of use to predict human reactions toward wildlife. The framework of this study is a combination of Planned Behavior Theory (TPB) and Wildlife Value Orientations (WVOs) that can identify and predict the behavior of farmers and ranchers in dealing with wildlife by creating a value-attitude-behavior cognitive hierarchy. The study was designed as a stratified random sample of 200 interviewees in Mazandaran province. We used the results (individual characteristics, questions related to conflicts, WVOs, and TPB variables) to analyze and predict the pro-environmental behavior of interviewees in conflict conditions. The results demonstrated that WVOs in total could predict 32% of TPB variables. The attitude and perceived behavior control variables had significant effects on behavioral intention (Respectively, (β = 0.49, p < 0.001) and (β = 0. 21, p < 0.05), and in total, these variables can predict 22% of the pro-environmental behavioral, whereas subjective norms had none. Most notably, combining two theories significantly enhanced the predictive power and comprehensiveness of the ultimate framework for predicting farmers' and ranchers’ pro-environmental behavior. The findings provide a clearer perception of factors driving the non-environmental behavior toward wildlife in conflict situations. So, the TPB and WVOs can be effective tools for investigating and reducing HWC. Also, they can be a basis for developing human-based conflict research in Iran.